Relationships among territory size, body size, and food availability in a specialist river duck - Ippi, Silvina Graciela (2018)
Models of territorial behaviour predict a reduction in territory size when food availability and competitive pressure increase. Moreover, body size can play an important role in territorial defence. The Torrent Duck (Merganetta armata) is a river specialist that exhibits year-round territorial behaviour and long-term pair bonds. Food availability measured as biomass of invertebrates per unit area, territory and body size of Torrent Ducks were studied in the Andes in Argentina to test predictions of territoriality models. The availability of aquatic invertebrates decreased with latitude, while territory size increased. As expected, territory size of Torrent Ducks showed a negative relationship with the availability of aquatic invertebrates, a major food source for Torrent Ducks. Larger males and females paired together and occupied territories with greater food availability. Body size may be important for both males and females for the successful acquisition and defence of territories, especially during the non-breeding season when the contest winner acquires or maintains the territory and the mate. Our results suggest that Torrent Duck specialisation on fast-flowing mountain rivers leads to year-round territoriality in both sexes, a positive correlation between territorial defence and body size, and territory size proportional to food availability and population density.